Scar endometrioma following obstetric surgical incisions: retrospective study on 33 cases and review of the literature - Leite, Guilherme Karam Corrêa; Carvalho, Luis Fernando Pina de; Korkes, Henri; Guazzelli, Thiago Falbo; Kenj, Grecy; Viana, Arildo de Toledo (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: The incidence of scar endometrioma ranges from 0.03 to 3.5%. Certain factors relating to knowledge of the clinical history of the disease make correct diagnosis and treatment difficult. The aim here was to identify the clinical pattern of the disease and show surgical results. The literature on this topic was reviewed. DESIGN AND SETTING: Retrospective descriptive study at Hospital Municipal Maternidade - Escola Dr. Mário de Moraes Altenfelder Silva. METHODS: Data from the medical records of patients with preoperative diagnoses of scar endometrioma who underwent operations between 2001 and 2007 were surveyed and reviewed. The postoperative diagnosis came from histopathological analysis. The main information surveyed was age, obstetric antecedents, symptoms, tumor location, size and palpation, duration of complaint, diagnosis and treatment. All patients underwent tumor excision with a safety margin. RESULTS: There were 33 patients, of mean age 30.1 ± 5.0 years (range: 18-41 years). The total incidence was 0.11%: 0.29% in cesarean sections and 0.01% in vaginal deliveries. Twenty-nine tumors (87.9%) were located in cesarean scars, two (6.0%) in episiotomy scars and two (6.0%) in the umbilical region. The main symptom was localized cyclical pain (66.7%), of mean duration 30.5 months (± 23). Surgical treatment was successful in all cases. CONCLUSION: This is an uncommon disease. The most important diagnostic characteristic is coincidence of painful symptoms with menstruation. Patients undergoing cesarean section are at greatest risk: relative risk of 27.37 (P < 0.01). The surgical treatment of choice is excision of the endometrioma with a safety margin.